KEANEKARAGAMAN MIKROALGA DI BENDUNGAN BARATA DESA E.WONOKWERTO KABUPATEN MUSI RAWAS - Dian Selviana; Harmoko Harmoko; Destien Atmi Arisandy (UNIVERSITAS PGRI MADIUN, 2021)
This study aims to determine the diversity of microalgae in the Barata Dam area, E. Wonokerto Village, Musi Rawas Regency. This research is included in quantitative descriptive research, this study uses a survey method by taking samples of microalgae in the Barata Dam Area, E. Wonokerto Village, Musi Rawas Regency, then the sample is examined at the Biology Laboratory of STKIP-PGRI Lubuklinggau. Types of microalgae found in the Barata Dam, E. Wonokerto Village, Musi Rawas Regency, 3 Divisions, 5 Classes, 14 Orders, 15 families, 15 genera and 15 species. The data that has been obtained from the research is then analyzed using the formula (Shannon-winer). The results of the diversity index of microalgae species at station I are 2,479, at station II the diversity index is 2,550 and at station III the diversity index is 2,836, the average diversity index from the three stations is 2,622 the index is classified as moderate. The types of microalgae from the Bacillariophytaceae class consist of 6 species including: Synedra ulna, Cylotella sp., Asterionella sp., Surirella sp., Tablelaria sp., and Rhizosolenia sp., Chlorophyceae class consists of 6 species including: Pleurotaenium sp. , Spirogyra sp., Closteridium sp., Selenastrum sp., Pediastrum duplex, and Microspora sp., Trebouxiophyceae class consists of 1 species namely: Chlorella sp., Ulvophyceae class consists of 1 species namely: Ulothrix sp., and Chyanophyta class consists of of only 1 species, namely: Oscillatoria sp., Abiotic factors found in the Barata Dam Area, E. Wonokerto Village, Musi Rawas Regency, namely: temperature (water) with an average (27.6 C), pH (water) with an average (7.7 ) and brightness (water ) with an average (76.1 Cm).